Pewarisan Makna Simbolik Peretuq / Peretus Dalam Tradisi Pengobatan Di Dusun Paokkambut Kecamatan Labuapi Lombok Barat - Muhammad Ijlal Sasakki Junaidi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The Peretuq tradition in Paokkambut Hamlet is a cultural heritage of the Sasak people that continues to survive amid modern influences. This ritual combines spiritual, social, and symbolic elements into a complex healing system. It functions not only as an alternative treatment for supernatural disturbances but also as a means of personal transformation and recovery. Using Victor Turner’s ritual theory, Peretuq is understood as a liminal process guiding individuals from separation to spiritual and social reintegration. Ritual stages such as body measurement, crown pulling, chanting of mantras, and application of sembe’ represent symbolic communication with transcendent forces. Beyond spiritual healing, the tradition reflects a unique blend of local wisdom and Islamic values. Thus, Peretuq plays a vital role in maintaining cultural identity, social solidarity, and spiritual balance within Sasak society.